COMPARATIVE NEUROCRANIAL MORPHOLOGY OF NIGERIAN BREEDS OF SHEEP - Atabo, Shaibu Mohammed; Umar, Abubakar Abubakar; Shehu, Sani Abdullahi; Abubakar, Adamu Abdul (Archives of Veterinary Science, 2022)
Este estudo estabeleceu a morfologia e a variação do neurocranium das raças nigerianas de ovelhas. Foram utilizadas 1.008 cabeças de raças Balami, Uda e Yankasa.O método de maceração de água quente foi adotado na preparação do crânio. As três raças tinham 6 ossos neurocraniais. O esquama occipital foi extenso em Balami e Uda das três raças, foi côncavo em fêmeas e convexo em machos, em Balami e Uda, a protuberância occipital externa foi proeminente em machos embora rudimentares em ambos os sexos de Yankasa, entre as três raças, raça e polimorfismo sexual foi observado nas cristas medianas e cristas nucal, e tubérculos rostral e muscular. A parte caudal do osso frontal das raças foi mais convexa em fêmeas do que em machos, enquanto a parte craniana é deprimida e aproximadamente achatada em fêmeas e machos, respectivamente. O Crista Galli do ethmóide era mais espesso em Balami do que Uda e rudimentar em Yankasa. O osso interparietal estava ausente tanto em jovem quanto em adulto, o parietal foi emparelhado no jovem, mas solteiro no adulto. Os ossos do neurocranium apresentaram variações dimórficas e polimórficas com diferenças sexuais entre as três raças. This study established the morphology and variation of the neurocranium of Nigerian breeds of sheep. A total of 1,008 heads of abattoir-slaughtered Balami, Uda, and Yankasa breeds were used. The hot water maceration method was adopted in the skull preparation. The three breeds had 6 neurocranial bones. The occipital squama was extensive in Balami and Uda of the three breeds, it was concave in females and convex in males, in Balami and Uda, the external occipital protuberance was prominent in males though rudimentary in both sexes of Yankasa, among the three breeds, breed and sex polymorphism was observed in the median and nuchal crests, and rostral and muscular tubercles. The caudal part of the frontal bone of the breeds was more convex in females than in males, while the cranial part is depressed and roughly flattened in females and males respectively. The Crista Galli of the ethmoid was thicker in Balami than Uda and rudimentary in Yankasa. The interparietal bone was absent in both young and adult, the parietal was paired in the young but single in the adult. The bones of the neurocranium showed dimorphic and polymorphic variations with sex differences among the three breeds.